2022
DOI: 10.1002/cyto.b.22080
|View full text |Cite
|
Sign up to set email alerts
|

CD200 expression on Sezary cells: A valuable tool for flow cytometric assessment of peripheral blood T‐cell neoplasms

Abstract: Background: CD200 (OX-2) is a valuable marker in the diagnosis of B-cell neoplasms and is commonly used in the screening panels for assessment of peripheral blood Bcell lymphoproliferative disorders. However, there is limited understanding about CD200 expression in T-cell neoplasms. A previous study has shown that CD200 is expressed on the neoplastic cells of angioimmunoblastic T-cell lymphoma (AITL) by immunohistochemistry, but no study has evaluated CD200 expression in T-cell neoplasms by flow cytometry. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…These are not the only advantages of minimizing the number of staining tubes, in that when samples are paucicellular, more diagnostic information also becomes further available utilizing the least number of tubes or wells cells are processed in. The more analytic power the clinical flow cytometry laboratory can harness, the more flexibility we can offer and better questions we can ask such as those described just above related to MRD as well as so many other areas(Estevam et al, 2021;Quir os-Caso et al, 2022;Shameli & Roshan, 2022;Sanjabi & Lear, 2021). Such hardware, reagents and software already exists in our research flow cytometry laboratories; we are all left waiting for these to move fully into the clinical realm, and to see advances in this area brings us all closer to far better laboratory practice.In the submission ofHammerich et al (2023), we learn of the application of a three-laser spectral flow cytometer demonstrating the analysis of a 31-marker clinically oriented testing panel.…”
mentioning
confidence: 99%
“…These are not the only advantages of minimizing the number of staining tubes, in that when samples are paucicellular, more diagnostic information also becomes further available utilizing the least number of tubes or wells cells are processed in. The more analytic power the clinical flow cytometry laboratory can harness, the more flexibility we can offer and better questions we can ask such as those described just above related to MRD as well as so many other areas(Estevam et al, 2021;Quir os-Caso et al, 2022;Shameli & Roshan, 2022;Sanjabi & Lear, 2021). Such hardware, reagents and software already exists in our research flow cytometry laboratories; we are all left waiting for these to move fully into the clinical realm, and to see advances in this area brings us all closer to far better laboratory practice.In the submission ofHammerich et al (2023), we learn of the application of a three-laser spectral flow cytometer demonstrating the analysis of a 31-marker clinically oriented testing panel.…”
mentioning
confidence: 99%
“…These findings were confirmed by CD200 immunohistochemical staining of tissue specimens. Based on these findings, authors have concluded that CD200 is commonly expressed on circulating Sezary cells, a feature that can potentially improve the diagnostic capacity of flow cytometry for the assessment of T‐cell neoplasms (Guitart, 2020; Horna et al, 2020; Lyapichev et al, 2020; Shameli & Roshan, 2022).…”
mentioning
confidence: 99%
“…The role played by these immunological markers in discriminating normal and aberrant plasma cells (NPC and APC, respectively) has been discussed, providing further insights into plasma cell characterization through the artificial eyes of flow cytometry (Das et al, 2022;Jevremovic & Olteanu, 2019;Mestrum et al, 2020;Oliveira et al, 2019;Zannetti et al, 2020;Zannetti et al, 2021). Based on these findings, authors have concluded that CD200 is commonly expressed on circulating Sezary cells, a feature that can potentially improve the diagnostic capacity of flow cytometry for the assessment of T-cell neoplasms (Guitart, 2020;Horna et al, 2020;Lyapichev et al, 2020;Shameli & Roshan, 2022). obtain more cells from limited needle puncture samples, the authors adopted a careful mechanical technique, in which tissue strips were gently pressed by a syringe piston.…”
mentioning
confidence: 99%